LEVERAGE EFFECT BETWEEN ISLAMIC STOCK AND SRI INDICES: CASE OF INDONESIA - Nur Dhani Hendranastiti (Ultima Management : Jurnal Ilmu Manajemen, 2022)
Abstract- This paper examines the difference in leverage effect between the Islamic stock index and the SRI index using the Indonesian data for a period before and during-after the COVID-19 pandemic. The interrelated issues of health and environment, starting from the COVID-19 pandemic, energy use, and environmental issues can have a different effects on different asset classes. With the distinctive feature of the Islamic stock index and SRI index, it can attract investors who want to diversify their portfolio to hedge against the health and environmental crisis. This study aims to examine the volatility risk in ISSI and SRI-Kehati as an impact of various events in 2020-2022. This paper attempts to test the leverage effect for a longer period incorporating the various major events in 2020-2022. This study uses daily price index data of ISSI and SRI-Kehati Index for the period 10/04/2013-28/11/2022 and employed the ARMA-EGARCH models to answer the objectives. The results show that there is a leverage effect in ISSI and SRI-Kehati for a period before and during-after the COVID-19 pandemic although the magnitude is lower after the during-after pandemic. The leverage effect indicates that the negative return that occurred in the constituents of both indices leads to higher volatility, implying that both indices are not prone to various events. The lower magnitude of the leverage effect on SRI-Kehati can give better assurance for investors regarding the volatility risk of the index. Keywords: Islamic Stock Index; SRI Index; COVID-19; Crisis; Leverage Effect